Determining effectiveness of dungeness crab escapement in derelict traps. (March 2023) - Antonelis, Kyle; Drinkwin, Joan; Rudell, Paul; Morgan, Jason; Selleck, James; Velasquez, Donald; Rothaus, Don P.
Abstract: The prevalence and impacts of derelict crab traps in the Washington waters of the Salish Sea have been well documented. When properly equipped with biodegradable escape cord, a derelict trap becomes "disabled" upon escape cord degradation, allowing an egress route for entrapped crab to escape. However, among trap designs commonly used in the region, the effectiveness of escapement (egress) varies. We conducted a laboratory experiment simulating derelict traps to analyze the escapement effectiveness of 13 recreational trap designs, some with modifications. The least successful trap designs in allowing crab escapement require crab to push open a door on the topside of the trap, offset from the edge. Escapement effectiveness in these traps improved when equipped with a bungee to spring-load the door open upon escape cord degradation, but escape rates were still not maximized. The traps most successful at allowing crab escapement were those that provided an unobstructed escape panel either on the wall or along the topside edge of the trap. Traps not designed with this feature can be easily modified by detaching one escape ring, and re-attaching it with escape cord. Following escape cord degradation, the ring falls away resulting in an opening through which the crab can freely escape. This study provides the first reporting of escapement effectiveness from derelict crab traps of the region, and results are currently influencing resource management and gear manufacturing decisions with intent to reduce Dungeness crab mortality from derelict traps. Highlights: Effectiveness of crab escapement from derelict trap designs is variable. An unobstructed escape panel on the wall or topside edge of trap is most effective. Topside hinged doors offset from trap edge are least effective. Simple trap modifications can increase effectiveness of escapement.